Assessment and Management of Lumps on the Face: A Guide for the General Dental Practitioner. Issue 3 (August 2017) - Cobb, Richard; Dungarwalla, Mohammed; Stenhouse, Philip
There are a number of conditions that can present as a lump on the face. The general dental practitioner is uniquely trained in head and neck anatomy and pathology and should be able to identify these important conditions and consider appropriate investigations. Understanding what requires urgent specialist assessment and what can be referred routinely can be difficult, but is crucial to high quality patient outcomes. This article aims to simplify common conditions that may present as a lump on the face or be an incidental finding within the primary dental care setting. It is by no means an exhaustive description of all the pathology that may be encountered within this anatomical region, however it should form a useful and practical framework for common presentations.